How to ensure no-one uses your theory of change: Lessons from the fron t lines of theory of change facilitation and possibilities for renewal - Tangelder, Mary (Theories of Change in Reality, 2024)
This essay discusses how theory of change can be used as a design tool to help funders and their grantees shift from short-term, discrete ac tivities to addressing deeper, systems-level change. Facilitating a th eory of change design process as part of an effort to co-design a stra tegy should, ideally, lead to a strategy that highlights collective ef forts and ultimately stimulates meaningful and powerful collaboration. Yet, engaging programme teams and grantees in theory of change has be en notoriously difficult, particularly given power dynamics between fu nders and grantees. Drawing from experience, this essay discusses blin d spots and typical stumbling blocks in theory of change design. It bu ilds a case for why we need to rethink and reimagine how to use this t ool to inspire action, build shared ownership, drive learning and adap tation, and ultimately accelerate the path to change.